Information sources affecting consumer behaviour in the electricity market - Czarnecka, Marzena (Management Sciences, 2018)
Electricity is a factor that facilitates the functioning of consumers in society and creates appropriate conditions for work, development and rest. Due to the scale and pace of the changes resulting from technological progress and new regulations, consumers in the electricity market do not have the appropriate technical, economic or legal knowledge. The most significant problems within the electricity market in Poland include the high level of ignorance of the services, institutions and basic terms required for making rational decisions in the electricity market. This is necessary in order to determine the sources from which consumers derive knowledge about the electricity market. Based on the research carried out by the author, it can be argued that the knowledge and skills concerning an evaluation of the electricity market, the institutions operating therein and their product are very low
Management Sciences, 2018, vol. 23, no. 2, s. 4-11
Keywords: consumer behaviour in the electricity market; electricity; consumers; zachowania konsumentów na rynku energii elektrycznej; energia elektryczna; konsumenci